Multiple Hippocampal Transections: Initial Clinical Experience with Modified Technique - Šroubek, Jan; Krámská, Lenka; Nová, Michaela; Červenka, Matěj; Míková, Barbora; Česák, Tomáš; Klener, Jan; Kovář, Martin; Vojtěch, Zdeněk (World neurosurgery, 2025)
OBJECTIVE: Standard resective treatment of mesial temporal lobe epilepsy (MTLE) includes anteromesial temporal resection or amygdalohippocampectomy. One potential risk of these surgeries, especially in patients with magnetic resonance imaging (MRI)-negative findings, is postoperative memory impairment. An alternative to resective procedures that aim to preserve the neuropsychological profile are multiple hippocampal transections (MHTs). The objective of transections is to interrupt the longitudinal pathways of the hippocampus to prevent the spread of epileptic seizures while preserving the memory circuits. Previously performed MHT procedures were guided by questionable intraoperative electrocorticography. At our institution, we have developed and tested a modified technique to achieve complete MHTs. METHODS: Patients with pharmacoresistant unilaterally lateralized MTLE and MRI-negative findings with high risk of neuropsychologic deterioration were indicated for complete MHT. Comprehensive neuropsychological and epileptological evaluations and MRI follow-ups were conducted 1 year and 2 years postoperatively. The primary evaluated parameters were seizure reduction and significant changes in neuropsychological performance (± 1 SD). RESULTS: Complete MHTs were performed on 3 patients who completed 2-year follow-up. Two MHTs were performed on the right and 1 on the left side. Two patients are classified as Engel 1 and one patient as Engel 3. Two years after surgery, neuropsychologic evaluation did not show significant decrease in memory performance and performance in majority of cognitive tests. One-year MRI follow-up showed decrease of volume of hippocampus in all 3 patients. CONCLUSIONS: This modified technique of MHT in patients with MTLE and MRI-negative findings led to seizure reduction while preserving their neuropsychologic performance.
Keywords: výsledek terapie; Young Adult; neurochirurgické výkony; Male; magnetická rezonanční tomografie; mladý dospělý; následné studie; Adult; dospělí; mužské pohlaví; Follow-Up Studies; Neuropsychological Tests; Treatment Outcome; Hippocampus; lidé; ženské pohlaví; Humans; Drug Resistant Epilepsy; refrakterní epilepsie; Epilepsy, Temporal Lobe; Neurosurgical Procedures; neuropsychologické testy; Magnetic Resonance Imaging; Female; lidé středního věku; epilepsie temporálního laloku; hipokampus; Middle Aged